Utilization of Herschal-Bulkley fluid in an inclined compliant channel. (July 2020) - Javed, M.; Iqbal, T.; Rao, A.I.; Hatami, M.
Abstract: This research addresses the impact of peristaltic flow of the Herschel-Bulkley fluid in two-dimensional flexible compliant channel. The effects of heat and mass transfer are deliberated by taking a non-uniform channel. Moreover the inclined nature of the channel has been taken into account. Using low Reynold's number and long wavelength assumptions, the governing system of non-linear differential equations is solved using perturbation technique. Expressions for the series solution for the fluid temperature, concentration and velocity field along with heat transfer coefficient are computed. Influence of various pertinent parameters are presented and discussed through graphs. Moreover, thinning and thickening nature of Herschel-Bulkley fluid is also explained through the graphs.